1982
DOI: 10.1111/j.1365-2044.1982.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective transcutaneous nerve stimulation following epidural anaesthesia

Abstract: Summary Thirty‐five patients were delivered by elective Caesarean section under general or epidural anaesthesia. For postoperative analgesia they received narcotic analgesics as required and either transcutaneous nerve stimulation or an inactive stimulator. The patients receiving an active stimulator following general anaesthesia had significantly less pain and required significantly less postoperative analgesia than their control group. The epidural patients did not receive any additional benefit from active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In the 10 trials that used assumed non‐optimal TENS treatment (Davies, 1983; Warfield et al, 1985; Galloway et al, 1984; Conn et al, 1986; Forster et al, 1994; Smedley et al, 1988; Navarathnam et al, 1984; Sim, 1991; Cuschieri et al, 1985; McCallum et al, 1988), the MWD in analgesic consumption between active TENS and placebo TENS was 4.1%, which was not statistically significant ( p =0.56).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the 10 trials that used assumed non‐optimal TENS treatment (Davies, 1983; Warfield et al, 1985; Galloway et al, 1984; Conn et al, 1986; Forster et al, 1994; Smedley et al, 1988; Navarathnam et al, 1984; Sim, 1991; Cuschieri et al, 1985; McCallum et al, 1988), the MWD in analgesic consumption between active TENS and placebo TENS was 4.1%, which was not statistically significant ( p =0.56).…”
Section: Resultsmentioning
confidence: 96%
“…Better pain relief has been reported for patients using PCA when compared to patients that had to require analgesics from the hospital staff (Passchier et al, 1993). Epidural analgesia may also influence the result by lessening the effect of TENS (Davies, 1983). There is also evidence that TENS is less effective after major surgical interventions like thoracotomy (Benedetti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although transcutaneous electrical nerve stimulation (TENS; applied via surface electrodes) is used as a minimally invasive treatment option by patients, it may cause discomfort due to activation of cutaneous nerve endings or skin irritation at the stimulation intensities required to activate the deep pain‐relieving nerve fibers, leading to low rates of patient compliance or ineffective treatment at comfortable intensities . Interestingly, although some payer coverage policies require that a patient have a positive response to TENS prior to undergoing peripheral nerve stimulation (PNS), TENS has not been found to be a reliable predictor of PNS efficacy .…”
Section: Introductionmentioning
confidence: 99%
“… 36 , 37 In retrospective studies, Smith et al 36 and Hollinger 37 demonstrated lower pain scores among patients treated with TENS devices at frequencies of 85 and 100 Hz, respectively. In a randomized trial of 35 patients, 38 Davies found lower pain scores and analgesic use among patients who received general anesthesia and active TENS treatment at 25 Hz compared with placebo, but no benefit in the group of patients who received epidural anesthesia. Interpretation of these studies is limited by their small sample size, lack of randomization or blinding, and changes in anesthetic care for cesarean delivery since their publication.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In retrospective studies, Smith et al 36 and Hollinger 37 demonstrated lower pain scores among patients treated with TENS devices at frequencies of 85 and 100 Hz, respectively. In a randomized trial of 35 patients, 38 Davies found lower pain scores and analgesic use among patients who received general anesthesia and active TENS treatment at 25 Hz b Pain was assessed using the BPI, which includes rating mean pain in the previous 24 hours using a numerical scale from 0-10, with 0 representing no pain and 10 the worst pain imaginable.…”
Section: Discussionmentioning
confidence: 99%